(untitled) (SCIENCE TIME JOURNAL, 2026)
In the context of globalization processes, multilingual competence is increasingly recognized as an indispensable professional and strategic asset in international relations. This research is devoted to a comprehensive analysis of the contribution of language proficiency to diplomatic effectiveness, the implementation of "soft power" strategies, and the processes of intercultural dialogue and global partnership. Applying a qualitative analytical methodology, the article investigates the functional determinants of multilingualism within diplomacy, international structures, security cooperation, and economic integration. The research findings confirm the strategic significance of multilingual competence in optimizing negotiation potential, supporting mechanisms of preventive diplomacy, and strengthening international platforms of trust. The study concludes with a scientific justification that multilingual education must serve as a fundamental component of professional training programs for specialists in the fields of "International Relations" and "World Languages."